A dedicated implementation mechanism can eliminate the tobacco from the lives of human being - Govind Kumar Tripathi; Rana J Singh (Tobacco Induced Diseases, 2018)
Background and challenges to implementation India launched its National Tobacco Control Programme (NTCP) in 2007-08 in 9 states.We made intervention in 53 districts of 29 states. The Union Team provided technical and financial support in 40 districts of 20 states with the objective to build supportive political and administrative environment, establish and strengthen the system, institutionalise enforcement of provisions of National Legislation. An analysis conducted to understand that how effectively Tobacco can be eliminated from the lives of Human being.